Switching Gillnets to Longlines: An Alternative to Mitigate the Bycatch of Franciscana Dolphins (Pontoporia blainvillei) in Argentina - Berninsone, Leonardo G.; Bordino, Pablo; Gnecco, Martín; Foutel, Mariana; Mackay, Alice I.; Werner, Timothy B. (Frontiers in Marine Science, 2020)
The franciscana dolphin (Pontoporia blainvillei) is considered the most threatened cetacean in the South Western Atlantic due to bycatch in gillnet fisheries of Argentina, Uruguay, and Brazil. As gillnet fisheries operate in the same areas inhabited by dolphins, methods and strategies to reduce bycatch require particular attention. This study investigated the potential of switching gillnets to bottom longlines to reduce franciscana bycatch rates while maintaining economic returns in a small-scale artisanal fishery in Argentina. Trials were conducted in Bahía Samborombón and Cabo San Antonio between October 2004 and January 2007, in cooperation with artisanal fishermen who simultaneously fished using bottom longlines and gillnets. Target and non-target catch composition, fishing yield, catch size distribution and quality of catch, as well as bycatch of dolphins, sea turtles and interaction with sea lions were compared between the two fishing methods. An economic analysis of the fishery was performed to evaluate the potential to assess the profitability of switching fishing gears. Hauls of both gear types deployed simultaneously in the same locations showed similar fish catch composition and catch size with both gears but reduced catch of juvenile fishes in longlines. Bycatch of franciscana in bottom longlines was limited to only one dolphin in three consecutive years of trials, and no direct interaction between turtles and hooks were recorded. interaction with sea lions and sea turtles was reduced. The economic analysis showed financially acceptable perspectives under a five-year scenario. Reducing gillnet effort by switching to bottom longlines appears a practical approach to creating a sustainable fishery that could result in significant mitigation of current bycatch of franciscana dolphins in Argentina. However, implementation requires acceptance and compliance by the artisanal gillnet fishery.